A experiência vivida a partir da fibromialgia: um estudo realizado no Sudoeste do Paraná - Moras, Tagley Cristina (2023)
This work seeks to gather data to better understand the illness process under the lived experience, being one of the possible ways to include interventions for patients diagnosed with fibromyalgia (FM). For this purpose, a mixed and exploratory research study is presented, based on the selection of participants by convenience. For this purpose, data will be analyzed from structured and semi-directed interviews, based on psychological theory in existential-phenomenology (EF). The study will have the participation of a sample of patients who were referred by the Family Health Strategy (ESF) teams, or by Primary Care (PC) professionals from the municipalities that make up the 8th Regional Health of Paraná, to the Regional Center of Especialidades (CRE) located in Francisco Beltrão, PR, Brazil. In data collection, the socio-demographic and occupational questionnaire and the DASS-21 questionnaire (which measures depression, anxiety and stress) will be applied, as well as a semi directed interview, where the participant will be questioned, via guiding questions, addressing their experiences with FM. Subsequently, the data will be tabulated and systematized using Microsoft Excel, to be analyzed and discussed. Also, the transcripts of the interviews will be carried out, and, with the use of the NVIvo program, the analysis and data processing will be carried out. The objective is to discuss the lived experience of subjects (n=6) who experience the diagnosis of FM, through the narrative of life stories corroborating the data analysis, based on the Fundamentals of Phenomenological-Existential Psychology (FE). Apparently, the way of understanding life through work/domestic activities and perceptions of action in the world with little contact with who one is, and with who one is being in the face of the illness experience, seems to be the choice of “know-how-to-be” ” from the lived experience of the participants, where staying in action presents itself in front of this possible meaning of being and existing.